Effect of precursors on biosynthesis of monensins A and B - Pospísil, S; Cimburková, E; Krumphanzl, V; Vanĕk, Z (Folia microbiologica, 1985)
Precursors of monensins (acetate, propionate, butyrate, isobutyrate) affect the total production and the relative proportion of monensins A and B. Addition of propionate into the fermentation medium causes a prevalence of monensin B whereas butyrate and isobutyrate stimulate the production of monensin A and suppress the production of monensin B.
Keywords: Monensin; kyselina máselná; monensin; Isobutyrates; butyráty; Furans; kyselina octová; Acetic Acid; Butyric Acid; acetáty; furany; Acetates; Propionates; propionáty; Butyrates; isobutyráty; Streptomyces